Analisis Pengaruh Rasio Keuangan Terhadap Profitabilitas Pada Bank Devisa Yang Terdaftar Di BEI Periode 2017-2022 - Dina Fadhilah; Gregorius N. Masdjojo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study is to determine the effect of Net Interest Margin (NIM), Operating Costs on Operating Income (BOPO), Loan to Deposit Ratio (LDR), and Non Performing Loan (NPL) on Profitability as proxied by Return on Assets (ROA). This research uses data sourced from foreign exchange bank companies listed on the Indonesia Stock Exchange (IDX) starting from 2017-2022 and financial ratio reports obtained from the Financial Services Authority (OJK). The total number of foreign exchange bank companies listed on the IDX is 32 companies and those that enter the test criteria are 12 companies. The total panel data of 288 comes from 6 years of quarterly data for 12 Foreign Exchange Banks. The results of panel data regression analysis with the help of E-Views software show that the best estimation choice is Fixed Effect Model (FEM). Based on FEM output, it was found that the NIM variable had a positive and significant effect on Profitability (ROA). BOPO variables have a negative and significant effect on Profitability (ROA). And NPL has a negative and significant effect on Profitability (ROA). The LDR variable has no effect on Profitability (ROA). The coefficient of determination of this FEM model is 95%. Keywords: NIM, BOPO, LDR, NPL, Profitability, FEM